Startup Kaizen: uma metodologia ágil para desenvolvimento de software em startups - Leonessa, Nathália Maria Rapuano de Lira Novaes (2016)
The methodologies currently used by startups for market discovery and software development focus on a more agile and fast development, aiming to obtain learning about the potential market. Often, these methodologies set aside good software development practices to make the process faster and more dynamic, with constant end-user participation. If, on the one hand, the use of methodologies such as Scrum and RUP for software development can result in the development of technological solutions that are not used by users due to the lack of participation in software construction, on the other hand, they bring many benefits when it comes to project management and software quality. In contrast, the opposite occurs to the methodologies and tools currently used by startups, such as Lean Startup, Customer Development, Thinking Design and Business Model Canvas. These methodologies and tools focus on the discovery and validation of the market, without concern for the final quality of the product developed for the client, impacting directly. This impact can also be a waste of time in developing a product that no one will be able to use because of the large number of failures or even it never be finalized due to management problems. The lack of concern for good management of a development project, and its final quality, can do as much damage as the lack of approximation with the potential client. Moreover, in an environment of extreme uncertainty, unknown variables should be reduced in order to achieve overall development success, not just business models. The use of good Software Engineering practices may allow obtaining more information and technical data about the solution developed, which directly impact the user. This information can be used as a basis for decision making, thereby reducing risks related to final product quality and project management, making it easier for potential customers to use, and leaner development. In this sense, this work proposes a software development methodology for startups, Startup Kaizen (SK). SK integrates good practices of methodologies such as RUP and Scrum with methodologies focused on validation and market discovery, such as Lean Startup, Customer Development, Thinking Design and Business Model Canvas. This union of good software engineering practices with market discovery aims to minimize the risk variables for the creation of a new company, whether related to market or management and software quality. After the creation of Startup Kaizen, a case study was performed with its application with graduate students in Computer Science at the Federal University of São Carlos in Sorocaba. This application allowed the data collection to analyze the results in the form of a case study.